PENGARUH BEBAN KERJA DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN BANK MANDIRI TASPEN CABANG BENGKULU - Onsardi, Onsardi; Riastami, Indar (Yayasan Insani Mandiri Santani, 2023)
This study aims at 1) To determine the effect of workload on the performance of employees of Bank Mandiri Taspen Bengkulu Branch 2) To determine the effect of job satisfaction on the performance of employees of Bank Mandiri Taspen Bengkulu Branch 3) To determine the effect of workload and job satisfaction affect the performance of employees of Bank Mandiri Taspen Bengkulu Branch. This type of research is a quacitive approach. The method used in this study is the descriptive method. The population in this study is the entire performance of Bank Mandiri Taspen Bengkulu Branch employees totaling 52 employees. the sample amounted to 52 people performance of employees of Bank Mandiri Taspen Bengkulu Branch. Based on the results of research on the effect of workload and job satisfaction on employee performance at PT. Bank Mandiri Taspen Bengkulu, can be concluded as follows: There is a negative and significant influence of workload (X1) on employee performance (Y) of PT. Bank Mandiri Taspen Bengkulu Bengkulu. There is a positive and significant influence of job satisfaction (X2) on employee performance (Y) of PT. Bank Mandiri Taspen Bengkulu Bengkulu. Workload and job satisfaction together affect the performance of employees (Y) of PT. Bank Mandiri Taspen Bengkulu Bengkulu. Keywords: workload, job satisfaction, employee performance,